Nutrition for cyclists - Griffin, Jane (The Crowood Press, 2014)
This practical book shows cyclists how to design the right diet that will allow them to incorporate a rigorous training regime into a busy lifestyle. With more than 30 years' experience of working with sportsmen and women at the highest levels, Jane Griffin explains the background science behind her dietary advice, and addresses the day-to-day concerns of today's two-wheeled enthusiasts